Struktur dan Kebahasaan Teks Berita Siswa Kelas VII SMP Negeri 2 Ampek Nagari - Rianti, Deli; Tamsin, Andria Catri (YASIN, 2023)
This research aims to accomplish two objectives. First, to describe the structure found in the news texts of 7th-grade students at SMP Negeri 2 Ampek Nagari. Second, to describe the linguistic aspects of the news texts of 7th-grade students at SMP Negeri 2 Ampek Nagari. This study is a qualitative research using a descriptive method. The data for this research are the structure and language features of news texts written by 7th-grade students at SMP Negeri 2 Ampek Nagari. The research instrument is the researcher themselves, meaning that the researcher has the task of determining the research focus, selecting an informant as a data source, collecting data, assessing data quality, analyzing data, interpreting data, and drawing conclusions based on the research findings. Firstly, the writing skills of the news texts by 7th-grade students at SMP Negeri 2 Ampek Nagari do not yet utilize the appropriate structure of a news text. This is evident from the significant number of news texts written by students that lack the proper use of the 5W+1H news elements. Out of the 30 analyzed news texts, it was found that 9 news texts have the appropriate title structure, 15 news texts have the appropriate core news content, and 26 news texts have the appropriate news content. Secondly, in terms of language usage, the news texts written by 7th-grade students at SMP Negeri 2 Ampek Nagari already adhere to the five linguistic principles of news texts. Out of the 30 analyzed news texts, it was found that 24 news texts do not use single sentences appropriately, 26 news texts do not use compound sentences appropriately, 27 news texts do not use conjunctions or connectors that convey chronological meaning, 6 news texts do not use conjunctions or connectors that convey causality, and 25 news texts do not use pronouns or pronominals appropriately.